The Amish outcast's holiday return [large type] - Williams, Lacy (Love inspired., 2021)
"Grace Beiler's shocked when Zach Miller arrives at her family's farmhouse seeking forgiveness for his teenage mistake that cost her sister's fiancé his life. But when her father gives Zach a job, Grace gets to know the man he's become ... and starts to want more than friendship. Can love bloom amid hidden secrets and family grief, and give them a fresh start at Christmas?"--Back cover.